Medical use of vegetables in the practice of ancient doctors (based on the treatise of Quintus Gargilius Martial Medicinae ex oleribus et pomis). - Петришин, Марта Йосипівна; Загайська, Галина Михайлівна; Любімова, Оксана Василівна; Тодощук, Вероніка Георгіївна (Aluna Publishing House, Poland, 2023)
The aim: The aim of our study is to investigate the specifics of the use of vegetables for the prevention and treatment of diseases in the medical practice of the Roman Empire. Materials and methods: The research material was based on the surviving fragments of the Roman writer Quintus Gargilius Martial's Medicinae ex oleribus et pomis. The study relied on general scientific methods of analysis and synthesis, as well as the method of contextual analysis, descriptive and interdisciplinary methods.
Conclusions: Gargilius' treatise Medicinae ex oleribus et pomis is a valuable source of information on the use of vegetables, herbs, fruits, and nuts for the treatment and prevention of numerous diseases. Roman doctors highly valued the therapeutic and prophylactic properties of radish, pumpkin, cucumber, celery, beetroot, cabbage, turnip, rutabaga, lettuce, onion, garlic and other vegetables, and successfully used vegetables as a medicine to strengthen the immune system, enrich the body with vitamins and minerals, as well as for the prevention and treatment of wounds and injuries in surgery, various tumors and inflammations, diseases of the gastrointestinal tract, gynecological pathologies, fever, cough, diseases of the ENT organs and skin. For medicinal purposes, the Romans used leaves, stems, roots and seeds of various vegetable crops. The results of the study suggest the possibility of exploiting the therapeutic potential of vegetables in modern medicine.
Keywords: history of medicine, Gargilius, vegetables, treatment, complimentary alternative medicine